Circulating Th17 and Th1 cells expressing CD161 are associated with disease activity in rheumatoid arthritis. (May 2014) - Miao, J; Zhang, K; Lv, M; Li, Q; Zheng, Z; Han, Q; Guo, N; Fan, C; Zhu, P
Abstract : Objectives: To determine whether the percentages of major CD4+CD161+ T-cell subsets [T-helper (Th)17, Th1, and Th17/Th1] in peripheral blood are correlated with disease activity of rheumatoid arthritis (RA). Method: In 42 RA patients and 15 healthy controls (HCs), the percentages of interleukin (IL)-17- and/or interferon (IFN)-γ-producing CD4+CD161+ T cells and the plasma levels of related cytokines were assessed by flow cytometry and cytometric bead array (CBA) analysis, respectively. Disease activity was evaluated by the 28-joint Disease Activity Score (DAS28). Results: The percentage of circulating CD4+CD161+IL-17+IFN-γ− T cells (CD161+ Th17) in RA patients increased significantly and was higher in patients with active disease status (DAS28 > 3.2) compared with those with low disease status (DAS28 ≤ 3.2), and correlated positively with DAS28, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), IL-17, and IL-6 levels in RA patients. The percentage of circulating CD4+CD161+IL-17−IFN-γ+ T cells (CD161+ Th1) decreased and correlated negatively with DAS28, CRP, and ESR levels in RA patients, while the percentage of CD4+CD161+IL-17+IFN-γ+ T cells (CD161+ Th17/Th1) was unchanged in RA patients and was not correlated with RA disease activity. Conclusions: These data suggest that the percentages of circulating CD161+ Th17 and CD161+ Th1 cells in RA patients reflect the degree of disease activity. They support the hypothesis that Th17 cells are involved in the pathogenesis of RA and that CD161+ Th17/CD161+ Th1-cell imbalance may contribute to the development of RA.